Y se hizo la imagen del héroe nacional costarricense… Iconografía emblemática de Juan Santamaria. - Guillermo Brenes Tencio. (Historia Crítica, 2009)
This article presents an iconographic reading (interpretation) of Costa Rica’s national hero, Juan Santamaría. It examines two types of visual representation: the bronze statue of Juan Santamaría as a soldier, designed by the French sculptor, Aristide Onésime Croisy (1840-1899); and the oil painting, La Quema del Mesón, by the Costa Rican artist, Enrique Echandi Montero (1866-1959).